Influences on Student Satisfaction with School Teaching: Insights from a College in Shandong Province - Hui, Xiang (Scholar: Human Sciences, 2026)
Purpose: The study investigates the influence of five independent variables (Instructor Quality, Course Structure, Campus Life and Social Integration, Teacher Feedback Quality, and Education Quality) on one dependent variable (Student Satisfaction). Additionally, it aims to identify significant differences between variables. Research design, data, and methodology: The research employed the Index of Item-Objective Congruence (IOC) for validity and a Cronbach’s Alpha in a pilot test (n=50) for reliability. 238 valid responses from students in a College, Shandong Province, were analyzed by multiple linear regression to verify the significant relationship between variables. Following this, 30 students underwent an 18-week Intervention Strategic Plan (SP). Afterward, the quantitative results from post-SP and pre-SP were analyzed in the paired-sample t-test for comparison. Results: In multiple linear regression, the study revealed that Campus Life and Social Integration, Teacher Feedback Quality, and Education Quality impacted student satisfaction, while (Instructor Quality and Course Structure had no significant impact on student satisfaction. Finally, the results from the paired-sample t-test for comparison demonstrated a significant difference in student satisfaction between the post-SP and pre-SP stages. Conclusions: This research aims to improve students’ satisfaction with the school at LYT College, Shandong Province, China.